1997
DOI: 10.1093/bja/78.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clonidine on gastric emptying of liquids

Abstract: We have investigated the effects of clonidine on gastric emptying of liquids in 30 patients. In a double-blind, randomized design, clonidine 150 micrograms, morphine 10 mg or saline in 1 ml was given i.m. One hour later, the patient drank a paracetamol solution (1.5 g in 50 ml water). Venous blood samples were obtained every 15 min for 90 min thereafter. Plasma paracetamol concentrations were measured using high-pressure liquid chromatography and the area under the concentration-time curve was calculated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…The latter effect is likely mediated by the higher AD pressure gradient observed on high resolution manometry. These results provide a mechanistic explanation for reports that clonidine accelerates liquid emptying in healthy subjects and diabetic patients 15,36,37 . Specifically, this study suggests that the acceleration of liquid emptying by α 2 ‐adrenergic agonists observed previously is due not only to the effects on gastric tone, but also to reduced gastric secretion volume.…”
Section: Discussionsupporting
confidence: 77%
“…The latter effect is likely mediated by the higher AD pressure gradient observed on high resolution manometry. These results provide a mechanistic explanation for reports that clonidine accelerates liquid emptying in healthy subjects and diabetic patients 15,36,37 . Specifically, this study suggests that the acceleration of liquid emptying by α 2 ‐adrenergic agonists observed previously is due not only to the effects on gastric tone, but also to reduced gastric secretion volume.…”
Section: Discussionsupporting
confidence: 77%
“…In the dog, clonidine was shown to dose-dependently decrease acetaminophen plasma levels, suggesting a delayed GE [32]. In contrast, and as observed in our study, higher plasma acetaminophen concentrations have been observed in some patients treated with clonidine as compared with the control saline group [33]. Although the rate of acetaminophen absorption is considered as a marker of GE, other factors may affect plasma acetaminophen concentrations, such as possible interference of clonidine with acetaminophen elimination or increases in liquid absorption [32].…”
Section: Discussionsupporting
confidence: 71%
“…AP has been widely studied as a marker of gastric emptying, and is regarded as being effective and reliable 12,14,15 . Nevertheless, there are concerns that factors other than the gastric emptying rate may influence acetaminophen absorption 16 . Alpha 2 agonists, 17 increased absorption of fluid and electrolytes in the isolated ileum and colon in vitro; and opioids increased fluid absorption from the jejunum in anesthetized rats 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Alpha 2 agonists, 17 increased absorption of fluid and electrolytes in the isolated ileum and colon in vitro; and opioids increased fluid absorption from the jejunum in anesthetized rats 18 . However, it is uncertain whether drugs in these categories influence small intestinal absorption in the intact animal 16 . Another factor to consider is the influence of drug treatment on the metabolism of acetaminophen.…”
Section: Discussionmentioning
confidence: 99%